A Developed Robust Model and Artificial Intelligence Techniques to Predict Drilling Fluid Density and Equivalent Circulation Density in Real Time; Sensors; Vol. 23, iss. 14 - Al-Rubaii M. Mohammed; Al-Shargabi M. A. T. S. Mokhammed Abdulsalam Takha Sallam; Aldahlawi B. Bayan; Al-Shehri D. Dhafer; Minaev K. M. Konstantin Madestovich (2023, 2023)
Title screen